Inequalities in ventilation tube insertion procedures between Aboriginal and non-Aboriginal children in New South Wales, Australia: a data linkage study. Issue 11 (27th November 2013) - Falster, Kathleen; Randall, Deborah; Banks, Emily; Eades, Sandra; Gunasekera, Hasantha; Reath, Jennifer; Jorm, Louisa
Abstract : Objectives: Australian Aboriginal children experience earlier, more frequent and more severe otitis media, particularly in remote communities, than non-Aboriginal children. Insertion of ventilation tubes is the main surgical procedure for otitis media. Our aim was to quantify inequalities in ventilation tube insertion (VTI) procedures between Australian Aboriginal and non-Aboriginal children, and to explore the influence of birth characteristics, socioeconomic background and geographical remoteness on this inequality. Design: Retrospective cohort study using linked hospital and mortality data from July 2000 to December 2008. Setting and participants: A whole-of-population cohort of 653 550 children (16 831 Aboriginal and 636 719 non-Aboriginal) born in a New South Wales hospital between 1 July 2000 and 31 December 2007 was included in the analysis. Outcome measure: First VTI procedure. Results: VTI rates were lower in Aboriginal compared with non-Aboriginal children (incidence rate (IR), 4.3/1000 person-years; 95% CI 3.8 to 4.8 vs IR 5.8/1000 person-years; 95% CI 5.7 to 5.8). Overall, Aboriginal children were 28% less likely than non-Aboriginal children to have ventilation tubes inserted (age-adjusted and sex-adjusted rate ratios (RRs) 0.72; 95% CI 0.64 to 0.80). After adjusting additionally for geographical remoteness, Aboriginal children were 19% less likely to have ventilation tubes inserted (age-adjusted and sex-adjusted RR 0.81; 95% CI 0.73 to 0.91). After adjusting separately for private patient/health insurance status and area socioeconomic status, there was no significant difference (age-adjusted and sex-adjusted RR 0.96; 95% CI 0.86 to 1.08 and RR 0.93; 95% CI 0.83 to 1.04, respectively). In the fully adjusted model, there were no significant differences in VTI rates between Aboriginal and non-Aboriginal children (RR 1.06; 95% CI 0.94 to 1.19). Conclusions: Despite a much higher prevalence of otitis media, Aboriginal children were less likely to receive VTI procedures than their non-Aboriginal counterparts; this inequality was largely explained by differences in socioeconomic status and geographical remoteness.